Value Chain Development of IARI Variety of Carrot: A Training Need Assessment (Indian Journal of Extension Education, 2025)
The green revolution made India self-sufficient in food production. Over the years, due to technological interventions, the quantity of food production increased to new heights. However, the income of farmers did not improve proportionately. Lack of integration of farmers to sustainable value chains could be one factor contributing to it. Under this impression, the research was conducted to identify the training needs of the farmers in the area of value chain development of the Carrot commercial variety (cv.) Pusa Rudhira during 2022. A total number of 80 farmers were selected randomly from Nizampur, Delhi, and Peer Nagar Sodhana, Uttar Pradesh. A training need index was developed. The findings showed that 71.25 per cent of the farmers had medium to very high need of training in the area of value chain development. The most sought-after training needs were the use of herbicides, vermicomposting, prevention of rotting, and contract negotiation skills. The identified areas may be given due consideration while organising training programmes for farmers so that they can upgrade themselves to better value chains and earn more income.